Theory and applications of field-effect transistors - Cobbold, Richard S. C. (Wiley-Interscience, 1970)
The content is essentially divided into four parts: an introductory survey; fabrication; theory of junction-gate and metal-insulator semiconducto transistors; and circuit applications.